Effects of Cetyltrimethylammonium Bromide on the Toxicity of Gold Nanorods Both In Vitro and In Vivo: Molecular Origin of Cytotoxicity and Inflammation. Issue 3 (28th January 2020) - Jia, Yan Peng; Shi, Kun; Liao, Jin Feng; Peng, Jin Rong; Hao, Ying; Qu, Ying; Chen, Li Juan; Liu, Li; Yuan, Xia; Qian, Zhi Yong; Wei, Xia Wei
Abstract: The safety issues and immunological effects of nanosized materials have drawn considerable attention. Gold nanorods (Au NRs) have promising applications in biomedical diagnosis and therapy, but their biosafety and the mechanism underlying in vivo toxicity still remain to be explored. In this study, cetyltrimethylammonium bromide (CTAB) capped Au NRs and PEG modified Au NRs are both prepared, the cytotoxicity evaluation indicates that CTAB‐Au NRs of different ratios all exhibit cytotoxicity while PEG‐Au NRs show improved biocompatibility. Furthermore, it is investigated how the surface characteristics influence toxical effects of Au NRs both in vitro and in vivo. It is found that CTAB‐Au NRs can induce acute cell necrosis, which results in the leakage of damage associated molecular patterns (DAMPs) such as mitochondrial DNA (mtDNA), subsequently triggering pulmonary inflammation. It is also revealed that the inflammation caused by CTAB‐Au NRs is probably mediated by the stimulator of interferon genes (STINGs) signaling pathway. This study explores the cytotoxicity and inflammatory toxicity of CTAB‐Au NRs, and how the surface modification affects the toxicity. The molecular pathways for the induction of pulmonary inflammation in vivo are further characterized. These findings might be of importance for designing safer and better gold‐based nanomaterials in the future. Abstract : This study explores the cytotoxicity and inflammatory toxicity of cetyltrimethylammonium bromide gold nanorods, and how the surface modification affects the toxicity. The molecular pathways for the induction of pulmonary inflammation in vivo are further characterized. These findings might be of importance for designing safer and better gold‐based nanomaterials in the future.